Sensitivity of Alternaria blight pathogen (Alternaria brassicicola) to fungicides and its effects on yield contributing parameters of mustard - Rahman, Md Atikur; Fatema-Tuz-Zohura; Hamim, Islam; Meah, M Bahadur; Hossain, Muhammed Ali (Fundamental and Applied Agriculture, 2020)
Alternaria leaf blight caused by Alternaria brassicicola is an important disease of mustard in Bangladesh. Twelve commercial fungicides were assessed against Alternaria brassicicola Bangladeshi isolate PMIL-5 using poison food technique. Among these fungicides, three fungicides viz. Contaf 5EC (Hexa- conazol 50%), Rovral 50 WP (Iprodione 50%) and Autostin 50WP (Carben- dazim 50%) showed highly sensitive to A. brassicicola isolate PMIL-5 and inhibited the total mycelial growth at the lowest concentration 0.0125% in in vitro condition. Other fungicides were either partially effective or ineffective. Two fungicides viz. Contaf 5EC and Rovral 50WP were selected based on their in vitro performance sprayed in the field onto foliage of mustard plants in four different concentrations (0.0125%, 0.025%, 0.05% and 0.1%) to evaluate the Alternaria leaf blight incidence and severity and some yield contributing parameters in treated and control plots. Among the used fungicides, double spray of Contaf 5EC @0.1% concentration at 45 and 55 DAS showed better results in minimizing disease occurrence and frequency of Alternaria leaf blight disease as well as a significant positive impact on the yield parameters of mustard variety BARI Sharisha 14 in the field.